Masa Kanak Kanak Dalam Seni Lukis Kontemporer - Wahyu Putra Alja; Angga Elpatsa (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2024)
This work aims to visualize the author's childhood in the past that will never be repeated in contemporary painting. At that time every day the author enjoyed various games and activities that provided fun such as: playing ball, kites, playing old tires, jumping rope, playing bicycles, exploring.  The author recalls childhood in the past which was a period of transition from traditional games to modern games with gadgets and online games. Technology has changed and replaced traditional games to games that exist on technological media such as games in mobile phones (cellphones). The method of creating this work follows five stages, namely preparation, looking for ideas and ideas. Then, at the elaboration stage, recall and talk with the author's childhood friends by looking back at the excitement and joy of childhood. In the third stage, the synthesis stage, choosing ideas that will be applied in a work of art. Next, the stages of concept realization, sketching and asking for the approval of the supervisor. Finally, the completion stage, presenting the painting work in the form of a final exhibition. The work featuring visualizations of the author's childhood consists of 10 works with the title, "Shepherd Boy", "Jumping Rope", "Playing Marbles", "After School", "Cycling", "Going Home Quran", "Brother", "Monitoring","Old Tires", "Kite Playing".